2020
DOI: 10.1016/s2213-2600(20)30105-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and attributable health burden of chronic respiratory diseases, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Background Previous attempts to characterise the burden of chronic respiratory diseases have focused only on specific disease conditions, such as chronic obstructive pulmonary disease (COPD) or asthma. In this study, we aimed to characterise the burden of chronic respiratory diseases globally, providing a comprehensive and up-to-date analysis on geographical and time trends from 1990 to 2017.Methods Using data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017, we estimated the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
590
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,330 publications
(644 citation statements)
references
References 30 publications
4
590
3
2
Order By: Relevance
“…14 Tobacco exposure is an important risk factor for the development of COPD. 15 Nearly one half of the patients in our study were former-smokers. This was different from other previous large-scale cross-sectional studies, in which the prevalence of former-smokers in COPD population was less than 20%.…”
mentioning
confidence: 72%
“…14 Tobacco exposure is an important risk factor for the development of COPD. 15 Nearly one half of the patients in our study were former-smokers. This was different from other previous large-scale cross-sectional studies, in which the prevalence of former-smokers in COPD population was less than 20%.…”
mentioning
confidence: 72%
“…Despite known weaknesses of this methodology, such as participant bias due to personal experiences; may result in classification error and underestimation or overestimation of measures. 74 The case studies used, deliberation with peers and the literature review was carried out before choosing the measures, to limit this and provide a robust list of measures. 36 Moreover, hierarchical regression analysis showed that the difference in the explanation of variances when Q1 -"The level of Experience and Knowledge of the participant" was added was of only approximately 2%.…”
Section: Resultsmentioning
confidence: 99%
“…There has not been a global COPD prevalence review conducted based on spirometry and standardised assessments for more than a decade, until this year, published as this was paper was being reviewed [ 32 ]. The results from our review of the global data estimate there to be 551,792,354 individuals suffering with COPD, the majority of whom are classed as GOLD moderate to severe.…”
Section: Discussionmentioning
confidence: 99%